2022
DOI: 10.1002/agt2.251
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study on fabrication of hollow poly(vinyl cinnamate) particles by particulate interfacial photocrosslinking

Abstract: Hollow polymer particles are widely used in various industries as coatings and thermal insulation materials. The encapsulation capabilities of various functional molecules and/or nanomaterials also provide access to applications such as drug delivery, heat storage, and catalysis, as well as self‐healing materials. In this study, we successfully fabricated hollow polymer particles from poly(vinyl cinnamate) (PVC) particles using LED light (λ = 265 nm) through interfacial photocrosslinking. Furthermore, we syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As illustrated in Figure a and Figures S60–S65 (Supporting Information), it can be plainly observed that the SF‐CMP 1.5 microspheres manifest aggregation reaction, interestingly accompanied by phagocytosis and fusion of the microspheres reminiscent of the biologic behaviors of the cells. This aggregation reaction probably originates from both inter‐ or intraparticle coupling [ 37 ] and particulate interfacial photocrosslinking [ 38 ] dominated by the Ostwald ripening mechanism. [ 39 ] The aberration‐corrected high‐angle annular dark field‐scanning transmission electron microscope (HAADF‐STEM) was used to provide solid evidence for dopants, surfaces, and interfacial defects in materials.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure a and Figures S60–S65 (Supporting Information), it can be plainly observed that the SF‐CMP 1.5 microspheres manifest aggregation reaction, interestingly accompanied by phagocytosis and fusion of the microspheres reminiscent of the biologic behaviors of the cells. This aggregation reaction probably originates from both inter‐ or intraparticle coupling [ 37 ] and particulate interfacial photocrosslinking [ 38 ] dominated by the Ostwald ripening mechanism. [ 39 ] The aberration‐corrected high‐angle annular dark field‐scanning transmission electron microscope (HAADF‐STEM) was used to provide solid evidence for dopants, surfaces, and interfacial defects in materials.…”
Section: Resultsmentioning
confidence: 99%
“…This approach simplifies the fabrication of various stimuli-responsive capsules by adding various functions to the starting materials (photoreactive spherical polymer particles). However, the interfacial photo-cross-linking was restricted to light sources with ultraviolet wavelengths, i.e., λ = 254−265 nm for cinnamate 34 and thymine 36 and λ = 365 nm for coumarin. 35 The introduction of substituents to functional groups to regulate the absorbance wavelength has been widely demonstrated in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial photo-cross-linking of polymer particles has been developed as a facile preparation route for various functional capsule polymer particles. In this approach, the [2 + 2] photodimerization reaction between photoreactive groups (e.g., cinnamate, coumarin, and thymine , ) is used as a cross-linking reaction between different polymer chains in particulate states. Furthermore, photoinduced cross-linking occurred only at the particle interfacial region owing to the photoabsorbance of the external light by the nonreacted cinnamate groups remaining in the polymer interfacial region.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer shell thickness of the hollow polymer particles could be regulated by changing the photoirradiation time and intensity. 31,32 Furthermore, capsule polymer particles were successfully prepared from hollow polymer particles by a posteriori encapsulation of various molecules. 33−35 To date, several photoreactive groups, such as cinnamate and coumarin, have been applied to interfacial photo-cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…The interfacial photoreaction led to shell-selective cross-linking of the polymer particles, and removing the non-cross-linked core polymers yielded hollow polymer particles. The polymer shell thickness of the hollow polymer particles could be regulated by changing the photoirradiation time and intensity. , Furthermore, capsule polymer particles were successfully prepared from hollow polymer particles by a posteriori encapsulation of various molecules. To date, several photoreactive groups, such as cinnamate and coumarin, have been applied to interfacial photo-cross-linking. , Using interfacial photo-cross-linking, pH-responsive capsules have been successfully prepared by copolymerizing additional pH-responsive monomers with photoreactive monomers. , …”
Section: Introductionmentioning
confidence: 99%